2016
DOI: 10.1103/physrevb.93.195423
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of ultrathin Fe films on W(110)

Abstract: The growth of one and two atomic layers of iron on a W(110) substrate was followed by low-energy electron microscopy. The near-surface structural properties of the perfectly flat pseudomorphic films were studied by quantitative low-energy electron diffraction analysis from areas of uniform thickness as well as by the density functional theory. A strong relaxation of the outermost atomic layers was found in Fe mono-and bi-layers on W(110). By calculating the phonon dispersion relations and phonon density of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Information about both types of the deformations can be obtained from the lattice dynamics studies, which to the best of our knowledge have not been yet reported for the Fe/BaTiO 3 interface neither for the clean BaTiO 3 surface. Since the significant changes in vibrational properties were observed in other nanosystems such as the Fe/W(1 1 0) [26][27][28], FeO/Pt(1 1 1) [29], and EuSi 2 /Si(0 0 1) thin films [30], similar effects can be expected in the Fe/BaTiO 3 interface.…”
Section: Introductionmentioning
confidence: 60%
“…Information about both types of the deformations can be obtained from the lattice dynamics studies, which to the best of our knowledge have not been yet reported for the Fe/BaTiO 3 interface neither for the clean BaTiO 3 surface. Since the significant changes in vibrational properties were observed in other nanosystems such as the Fe/W(1 1 0) [26][27][28], FeO/Pt(1 1 1) [29], and EuSi 2 /Si(0 0 1) thin films [30], similar effects can be expected in the Fe/BaTiO 3 interface.…”
Section: Introductionmentioning
confidence: 60%
“…The bulk lattice constant of bcc Fe is a Fe = 2.867 Å, and of bcc W is a W = 3.165 Å. Due to this large lattice mismatch, there is a considerable inward relaxation of the Fe layers, which has been confirmed by experimental [30][31][32] as well as theoretical [33][34][35] investigations. In our calculations the distance between the top W layer and the interfacial Fe layer was chosen to be 2.01 Å, while the distance between the interfacial and surface Fe layers was set to 1.71 Å, according to the results of earlier studies based on density functional theory calculations [34,35].…”
Section: B Ab Initio Calculationsmentioning
confidence: 79%
“…Since a DL of Fe grows pseudomorphically on W(110) [50], two-dimensional translational symmetry is applied throughout the whole system with the lattice constant of bcc bulk W (a W = 3.16 Å). According experimental [51] and theoretical [52] studies there is a considerable inward relaxation of the Fe layers due to the large lattice mismatch between Fe and W. Following Ref. 53, the Fe-W and Fe-Fe layer distances were chosen as 2.01 Å and 1.71 Å, respectively.…”
Section: Fe2au(001)mentioning
confidence: 99%